A Case with Fever of Unknown Origin Diagnosed as Wegener Granulomatosis - Emel Bayrak; Ömer Dönderici; Rüştü Serter; Fatma Kaplan Efe (Archives of Rheumatology, 2010)
Fever of unknown origin (FUO) was described in 1961 by Petersdorf and Beeson as a fever above 38.3°C that lasts more than three weeks and cannot be diagnosed despite a one-week hospitalized examination. In 1991, Durack and Street made a different FUO description for patients with nosocomial infections, human immunodeficiency virus (HIV) and neutropenia. Along with this reconsideration, the investigation period was limited to one week of investigation, three days of hospitalization or three clinical visits. In the literature, the most frequent cause of FUO is infections followed by neoplasms and connective vascular diseases, respectively. The etiology in 5-15% of patients can not be diagnosed despite detailed examination. Here, we present a 75-year-old patient admitted to the hospital with a two-week history of fever, fatigue and lack of appetite. He had been examined in the infection and lung diseases clinics over a three–month period without diagnosis. In our internal medicine clinic, we diagnosed the patient as Wegener granulomatosis and a satisfactory response to the therapy was observed. (Turk J Rheumatol 2010; 25: 159-61)